LAPAROSCOPIC CHOLECYSTECTOMY PERFORMED SIMULTANEOUSLY WITH RETROPERITONEOSCOPIC LIVING DONOR NEPHRECTOMY - D. V. Perlin; I. V. Aleksandrov; V. P. Zipunnikov; I. N. Dymkov (Вестник трансплантологии и искусственных органов)
The shortage of donor organs leads to a gradual extension of the selection criteria for living donors including age and presence of comorbidities. Performing simultaneous operations with donor nephrectomy would further increase the number of living donors and increase the attractiveness of operations. In this observation, the examination of a 60-year-old potential donor revealed a concomitant disease: chronic calculous cholecystitis, which had existed for over 20 years. Ultrasound examination of the abdomen showed a strong adhesion of the bowel to the anterior abdominal wall. To prevent the risk of damage to the abdominal organs, it was decided to perform the nephrectomy retroperitoneoscopically and a simultaneous cholecystectomy from the same access. This procedure has three major advantages: no contact with the abdominal cavity when performing the access, the easiest access to the renal arteries, and the absence of a systematic increase in intraperitoneal pressure. Such access is of particular importance for the patients who have had previous interventions on the abdominal organs.